2018
DOI: 10.4274/haseki.25743
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Quercetin on Intestinal Damage Caused by Ionizing Radiation

Abstract: Radyasyona Bağlı İntestinal Hasarda Quercetin'in Koruyucu EtkisiAim: The aim of this study was to evaluate the protective use of quercetin in a rat model of radiation-induced enteritis and colitis.Methods: Twenty four adult rats were randomly divided into four groups. Group SHAM was given only physiological saline, group QUER was given quercetin 50 mg/kg for 15 days, group RAD was given only irradiation and group QUER+RAD was given quercetin 50 mg/kg, and then irradiated. Twenty four hours after the exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…In addition, protective effects of QC on intestinal damage due to ionizing radiation were studied in the rat model of radiation-induced ileitis and colitis. This study confirmed that QC significantly decreased oxidative stress and inflammatory damage in both ileum and colon tissues [265]. To the best of our knowledge, there are no studies show the effects of QC on anaphylactic shock induced by IV iron administration.…”
Section: Cooperation Of Qc and Ionps In Memory Enhancementsupporting
confidence: 85%
“…In addition, protective effects of QC on intestinal damage due to ionizing radiation were studied in the rat model of radiation-induced ileitis and colitis. This study confirmed that QC significantly decreased oxidative stress and inflammatory damage in both ileum and colon tissues [265]. To the best of our knowledge, there are no studies show the effects of QC on anaphylactic shock induced by IV iron administration.…”
Section: Cooperation Of Qc and Ionps In Memory Enhancementsupporting
confidence: 85%
“…Research conducted so far on the role of garlic and onions in the prevention and alleviation of the course of diseases and ailments of the digestive tract is apparently insufficient, inconsistent, incomplete, and often contradictory. Moreover, they relate to various forms of garlic and onion use (fresh vegetables, fresh extract, freeze-dried forms, oil, and isolated compounds), supplementation time and dose, and finally various animal research models (e.g., rats [67][68][69][70][71][72][73], mice [74], pigs [75], broilers, and chickens [76][77][78][79]) with induced injuries of the gastrointestinal tract [67,69,71,73,74] or infected with pathogenic microorganisms [74]. In the available literature, no information was found on the effect of the addition of raw Alliaceae plants, administered in an atherogenic diet, on morphological changes in the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin could affect the progression of colitis and IBD [ 30 ] and possessed protective and beneficial effects on chronic intestinal inflammation [ 31 ]. It was used to treat inflammatory illnesses caused by mast cells [ 32 , 33 ], treat IBD induced by Citrobacter rodentium [ 34 ], and effectively decrease oxidative stress and inflammatory damage to both ileum and colon tissues [ 35 ]. Luteolin was reported to have strong anti-inflammatory activity [ 36 , 37 ] and strong radical scavenging and cell-protective properties [ 38 ].…”
Section: Resultsmentioning
confidence: 99%